2009
DOI: 10.3102/0002831209340042
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Contribution of Distributed Leadership to School Improvement and Growth in Math Achievement

Abstract: Although there has been sizable growth in the number of empirical studies of shared forms of leadership over the past decade, the bulk of this research has been descriptive. Relatively few published studies have investigated the impact of shared leadership on school improvement. This longitudinal study examines the effects of distributed leadership on school improvement and growth in student math achievement in 195 elementary schools in one state over a 4-year period. Using multilevel latent change analysis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
343
0
33

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(395 citation statements)
references
References 63 publications
19
343
0
33
Order By: Relevance
“…Vliv role lídra na výkon organizace je zásadní, výzkumy se snaží prokázat jeho přímé a nepřímé působení na různé prvky vzdělávacího systému (učitelé, studijní výsledky studentů aj.). Prokázání přímého vlivu stylu řízení ředitele na studijní výsledky studentů je do velké míry problematické a potvrzeny jsou zejména vlivy nepřímé (Grissom & Loeb, 2011;Hallinger & Heck, 2010;Heck & Hallinger, 2009;Louis, Leithwood, Wahlstrom & Anderson, 2010). Výzkumy zaměřující se na různé formy managementu a leadershipu jsou početné: "performance management" (P. Earley, Bubb, Eddy-Spicer, Crawford, & James, 2016;Page, 2016), "distributed leadership" (L. M. , "educational leadership" (Dorczak, 2014), "leadership for learning" (Malakolunthu, McBeath, & Swaffield, 2014), "transformational leadership" (Balyer, Karatas, & Alci, 2016;Finnigan, 2012), "district leadership" (Moorosi & Bantwini, 2016), coaching (Lochmiller & Karnopp, 2016) a mnohé další.…”
Section: Výsledky Rešeršeunclassified
“…Vliv role lídra na výkon organizace je zásadní, výzkumy se snaží prokázat jeho přímé a nepřímé působení na různé prvky vzdělávacího systému (učitelé, studijní výsledky studentů aj.). Prokázání přímého vlivu stylu řízení ředitele na studijní výsledky studentů je do velké míry problematické a potvrzeny jsou zejména vlivy nepřímé (Grissom & Loeb, 2011;Hallinger & Heck, 2010;Heck & Hallinger, 2009;Louis, Leithwood, Wahlstrom & Anderson, 2010). Výzkumy zaměřující se na různé formy managementu a leadershipu jsou početné: "performance management" (P. Earley, Bubb, Eddy-Spicer, Crawford, & James, 2016;Page, 2016), "distributed leadership" (L. M. , "educational leadership" (Dorczak, 2014), "leadership for learning" (Malakolunthu, McBeath, & Swaffield, 2014), "transformational leadership" (Balyer, Karatas, & Alci, 2016;Finnigan, 2012), "district leadership" (Moorosi & Bantwini, 2016), coaching (Lochmiller & Karnopp, 2016) a mnohé další.…”
Section: Výsledky Rešeršeunclassified
“…To secure and sustain school improvement, effective distributed leadership is generally demanded (TSE, 2006).Distributed leadership is defined as one of the forms of leadership that involves all the different forms of collaboration experienced by the principal, teachers, and members of the school's improvement team in leading the school's development (Heck & Hallinger, 2009). Fullan (2001)states that the notion of sustainable change in schools is based on distributed leadership among the school staff.…”
Section: Related Literaturementioning
confidence: 99%
“…We found that despite the various claims of positive effects of distributed leadership practices, very few studies that acknowledge the different patterns of leadership distribution (e.g., [59,[78][79][80]) and fewer (e.g., [81,82]) that examined their relations with organizational outcomes. Furthermore, literature shows that the majority of texts produced on distributed leadership were based on examination in the context of school and educational improvement and rarely in community engagement settings (e.g., [49][50][51][52][53][54][55][56][57][58][59][60][61][62]65,67,68]).…”
mentioning
confidence: 99%